On the transmit field inhomogeneity correction of relaxation‐compensated amide and NOE CEST effects at 7 T. (23rd January 2017) - Khlebnikov, Vitaliy; Windschuh, Johannes; Siero, Jeroen C.W.; Zaiss, Moritz; Luijten, Peter R.; Klomp, Dennis W.J.; Hoogduin, Hans
Abstract : High field MRI is beneficial for chemical exchange saturation transfer (CEST) in terms of high SNR, CNR, and chemical shift dispersion. These advantages may, however, be counter‐balanced by the increased transmit field inhomogeneity normally associated with high field MRI. The relatively high sensitivity of the CEST contrast to B 1 inhomogeneity necessitates the development of correction methods, which is essential for the clinical translation of CEST. In this work, two B 1 correction algorithms for the most studied CEST effects, amide‐CEST and nuclear Overhauser enhancement (NOE), were analyzed. Both methods rely on fitting the multi‐pool Bloch‐McConnell equations to the densely sampled CEST spectra. In the first method, the correction is achieved by using a linear B 1 correction of the calculated amide and NOE CEST effects. The second method uses the Bloch‐McConnell fit parameters and the desired B 1 amplitude to recalculate the CEST spectra, followed by the calculation of B 1 ‐corrected amide and NOE CEST effects. Both algorithms were systematically studied in Bloch‐McConnell equations and in human data, and compared with the earlier proposed ideal interpolation‐based B 1 correction method. In the low B 1 regime of 0.15–0.50 μT (average power), a simple linear model was sufficient to mitigate B 1 inhomogeneity effects on a par with the interpolation B 1 correction, as demonstrated by a reduced correlation of the CEST contrast with B 1 in both the simulations and the experiments. Abstract : At a B 1 of 0.43 μT, a linear B 1 correction algorithm sufficiently reduced B 1 inhomogeneity effects for both amide and NOE CEST. The image quality produced by the linear correction is similar to that of the interpolation‐based B 1 correction.